Developing a database for Cs-137 radioactivity concentration and assessing residual levels in surface soils of Quang Ninh, Hai Phong, and Lang Son provinces - An Trung Nguyen; Thi Cam Ha Nguyen; Tien Thinh Lai; Hoang Giang Nguyen; Ha Vu; Thanh Long Nguyen (Vietnam Journal of Science, Technology and Engineering, 2022)
The radioactivity concentration of Cs-137 was determined in 826 soil samples collected from Hai Phong, Quang Ninh, and Lang Son. The residual levels of Cs-137 have also been assessed and compared with previous publications to obtain a trend in Cs-137 in the surface soil. The actual measured average of the residual level of Cs-137 in the soil samples collected in this study was 236±146 Bq/m2, while the value calculated using the published experimental formula was 407±77 Bq/m2. The impact of Cs-137 deposition from the Fukushima nuclear accident (2011) in this area is confirmed to be negligible.